Enforcement operations public & private enforcement agencies - Yaacob, Samsudin (Universiti Putra Malaysia Press, 2017)
The objective of this book is to provide exposure and understanding of enforcement agencies, especially the state enforcement agencies and local authorities. Enforcement agencies, whether at the federal or state levels and whether in the public or private sector, play an important role in enforcing the country’s laws. This book is thus a very important reference and to some extent a guideline for enforcement agencies in dealing with tasks related to enforcement and operations.